PENGARUH MUTU MAKANAN DAN TANGIBLE TERHADAP KEPUASAN KONSUMEN OLIVE FRIED CHICKEN - Christin Puspitasari; Yunita Fitri Wahyuningtyas (STIE Wiyatamandala, 2023)
Research is aimed at looking food quality, tangible to olive fried chicken consumer satisfaction. This a quantitative descriptive research with a cross sectional research design. The population in this study were consumers or customers of Olive Fried Chicken. The number of samples in this study were 65 respondents. Data analysis in this study used multiple regression analysis. The classical assumption requirements that must be met by the multiple regression model before the data are analyzed are the normality test, multicollinearity test and heteroscedasticity test. There is a significant effect of product quality on consumer satisfaction at Olive Fried Chicken. There is a significant influence of the physical environment on customer satisfaction at the Olive Fried Chicken. There is a significant influence of product quality and physical environment on consumer satisfaction at Olive Fried Chicken Fast Food Restaurants.